The Societal Changes among the Tribes of Chittagong Hill Tracts - Mekhala Mekhala (Journal of Research and Multidisciplinary, 2019)
The study of the society of the tribes of Chittagong Hill Tracts, a south-eastern region of present Bangladesh is a significant area. Number of researches have come out on Chittagong Hill Tracts and its people, but the society of the tribes, with the passage of time how changes took place in their customs, traditions and culture etc. due to interaction with the outside world and spread of education have not attracted the attention of the scholars. Issues like origin of the tribes, political background, warfare among the tribes, their chief or king and their court, the royal families etc. have been researched. Many works that dealt with the Chittagong Hill Tracts and its people have not focused on the life of the tribes, their society, its norms and values which have their roots in the past are attributed especially on women that indicates the mind-set of the society. One finds difficulties with the sources as the historical records of this region begin only after the arrival of the British since they are also very scanty and scattered. In spite of it, this research has tried to dig out the nature of the society by using the available historical sources--writings of the British administrators, accounts of foreign travellers and the contemporary history of Arakan and Tripura, and alternative sources, like folk literature, oral traditions etc. and have attempted to focus on the insight of the society, by analysing different social institutions, like family, marriage etc. and other important factors, such as health, education, health. Hopefully, more works will come out on the tribes of Chittagong Hill Tracts, and the findings will give wider view of the tribal society